The Transcriptional Specificity of NF-κB Dimers Is Coded within the κB DNA Response Elements - Vivien Ya‐Fan Wang; Wendy Huang; Masataka Asagiri; Nathanael J. Spann; Alexander Hoffmann; Christopher K. Glass; Gourisankar Ghosh (2012)
Nuclear factor κB (NF-κB) regulates gene expression by binding to specific DNA elements, known collectively as κB sites, that are contained within the promoters/enhancers of target genes. We found that the identity of the central base pair (bp) of κB sites profoundly affects the transcriptional activity of NF-κB dimers. RelA dimers prefer an A/T bp at this position for optimal transcriptional activation (A/T-centric) and discriminate against G/C-centric κB sites. The p52 homodimer, in contrast, activates transcription from G/C-centric κB sites in complex with Bcl3 but represses transcription from the A/T-centric sites. The p52:Bcl3 complex binds to these two classes of κB sites in distinct modes, permitting the recruitment of coactivator, corepressor, or both coactivator and corepressor complexes in promoters that contain G/C-, A/T-, or both G/C- and A/T-centric sites. Therefore, through sensing of bp differences within κB sites, NF-κB dimers modulate biological programs by activating, repressing, and altering the expression of effector genes.